Development of a dynamic wallpaper selection method with measurement features using a mobile platform with augmented reality technology / Jasni Dolah, Nur Hazirah Abdul Manab and Liza Marziana Mohammad Noh - Dolah, Jasni; Abdul Manab, Nur Hazirah; Mohammad Noh, Liza Marziana (Faculty of Art and Design, 2021)
This study presents a dynamic wallpaper selection method with measurement features on a mobile platform using Augmented Reality Technology. Many wallpaper sellers only use catalogues that easily complicate a customer's selection process since customers cannot imagine how a wallpaper would look when mounted on the wall in their homes. This study aims to help customers save time by using their smartphones to select wallpapers before they actually go to the shop to purchase the wallpaper. A crucial step in the purchase of wallpaper using smartphones would be to use Augmented Reality with measuring features through mobile applications. This paper focuses on two main goals, namely to help customers save time while choosing a wallpaper using Augmented Reality (AR), and assisting customers to visualise what the wallpaper would look like once mounted on the walls in their homes. This study used a mix-method approach and applied the online survey method involving Universiti Sains Malaysia undergraduate students (n=20). Problem values, the use of calculation tools and the advantage of improved realism were evaluated and the average percentage was measured.